Design of GaAs HBT VCO Based on Response Surface Method - Li, Zhisen; Liu, Min; Zhang, Jincan; Xu, Kun; Zhang, Bowen; Huang, Tonghe; Wang, Yiming (Scientific Journal of Technology, 2025)
In this paper, a differential cross-coupled Colpitts voltage control oscillator (VCO) based on 1 µm GaAs HBT technology is presented, and response surface method (RSM) is used to co-optimize the phase noise, center frequency, and tuning range of the VCO. The differential cross-coupled structure is used to provide negative resistance and the Colpitts structure is applied for achieving low phase noise. Then, we choose five parameters of the VCO circuit through establishing RSM model, in order to find the optimal combination of VCO circuit design parameters and to obtain the best performance. The results show that the frequency tuning range of VCO circuit is 11.59~15.39 GHz, the phase noise is -110.6 dBc/Hz at 1 MHz offset from center frequency of 13.49 GHz, the power consumption of the VCO core is 18.05 mW at 5.0 V supply voltage and the calculated figure of merit (FOM) is -189.628 dBc/Hz. The performance of the VCO is improved after the optimization of response surface method.